Reduced Numbers of Returning Atlantic Salmon (Salmo salar) and Thiamine Deficiency Are Both Associated with the Consumption of High-Lipid Prey Fish - Marja Keinänen; Jari Raitaniemi; Jukka Pönni; Tiina Ritvanen; Timo Myllylä; Pekka J. Vuorinen (Fishes)
In 2023, exceptionally few salmon (Salmo salar) ascended from the Baltic Sea to spawn in the Rivers Tornionjoki and Simojoki, regardless of the proper number of smolts descending to the sea in preceding years. We investigated how the numbers of age-0 and young herring (Clupea harengus) and sprat (Sprattus sprattus), which are the principal prey species of salmon in the Baltic Proper, the main feeding area of these salmon, as well as the amount of lipid obtained from them and their protein-to-lipid ratio, correlated with the number of returning salmon and the thiamine (vitamin B1) status of spawning salmon. The fewer the 0-year-old herring were and the more abundant were the youngish sprat in the Baltic Proper when the post-smolts arrived there, and the greater the lipid content and lower the protein-to-lipid ratio of the prey fish, the fewer salmon returned to the Rivers Tornionjoki and Simojoki to spawn two years later. The number of returning salmon was lowest with a high ratio of youngish sprat, 1–3 years old, regarding the River Tornionjoki and 1–2 years old regarding the River Simojoki post-smolts, to 0-year-old herring, which were of a suitable size to be the prey for the post-smolts upon their arrival in the Baltic Proper. In 2021, the ratios were lowest due to the record-low number of 0-year-old herring. The poor thiamine status of spawning salmon was also associated with the high lipid content of available prey fish and with the abundance of youngish sprat, which have twice the lipid content of age-0 herring. Our findings parallel the observations in the early 1990s when post-smolt survival declined concurrently with the outbreak of thiamine deficiency, M74. We conclude that consuming high-lipid marine fish reduces the survival of post-smolts and, thus, the number of returning salmon, in addition to causing thiamine deficiency.